Application of a Six-Step Bionic Strategy for Achieving Product Segmentation - Elena Angeleska; Kristijan Vasilevski; Ile Mircheski; Sofija Sidorenko (TEM Journal, 2022)
In this paper, the six-step strategy for bionic inspiration in industrial design and engineering is improved with involvement of an additional tool - functional decomposition. The improved strategy is explained through a design case study. The case study uses a “bottom-up” approach for identifying the key functionalities of the dandelion flower which is recognized as a unique natural phenomenon. Those functionalities are then redefined in a technical manner and used for designing a solar street light with the goal to achieve unique aesthetics and segmentation (modularity). Тhe presented tools for systematization of gathered bionic information can help make the bionic product development processes more efficient.
Keywords: Bio-inspired design, Bionic six-step strategy, Functional decomposition, Dandelion flower, Street light